Retinoids: novel potential therapeutics in the pursuit of HIV-1 cure - Purssell, Andrew; McGuinty, Michaeline; Vulesevic, Branka; Angel, Jonathan B. (Frontiers in Virology, 2022)
Human immunodeficiency virus (HIV) infection remains a global epidemic. While antiretroviral therapy (ART) suppresses viral replication, cessation of ART results in viral rebound necessitating lifelong treatment. This is a result of a reservoir of latently infected cells, resistant to clearance by ART and the major obstacle in curing HIV. HIV cure strategies have focused on reactivating this latent reservoir with latency reversal agents (LRAs) along with enhancement of anti-HIV immunity to eliminate reactivated HIV. Retinoic acid (RA) derivatives are promising therapeutics that may promote clearance HIV latent reservoir allowing for definitive cure. In addition to plausible mechanisms for depleting the latent reservoir with LRA activity via the p300 acetyl transferase pathway, countering HIV-mediated suppression of RIG-I and IRF-3, and proposed induction of selective apoptosis of HIV-infected cells via RIG-I, RA may also limit HIV spread by augmenting cellular trafficking via CCR7 and CCR9 and induce accumulation of high-affinity effector CD8+ T cells that aid immune clearance of HIV-infected cells. Furthermore, due to their specificity for HIV-infected cells, retinoids are attractive agents to form the basis of multidrug regimens. Altogether, retinoids have many compelling properties as potential novel therapeutics in the cure of HIV.